Commercial Probiotics Improve Growth, Feed Efficiency, Nitrogen Removal, Hemocyte Count and Suppression of Vibrio Population in Pacific White Shrimp Culture - Utami, Diah Ayu Satyari; Ilham, Ilham; Insani, Liga; Kusmiatun, Anik; Wahyu, Wahyu; Yudiati, Ervia; Rahman, Rahman; Albasri, Hatim; Szuzter, Brian Walter (Marine Science Department Diponegoro University, 2025)
The Pacific white shrimp (Penaeus vannamei) is a key species in global aquaculture, particularly under intensive farming systems where high stocking densities often lead to deteriorating water quality, disease outbreaks, and reliance on antibiotics. While probiotics are increasingly applied to enhance shrimp health and performance, comparative evidence on the efficacy of different commercial probiotic formulations remains limited. This study aimed to evaluate the effects of three commercial probiotic products on growth performance, water quality, microbial populations, and immune response in intensively reared Pacific white shrimp. Shrimp were fed diets supplemented with one of three probiotics (PB, PL, and PMB) or a control diet for 40 days. Growth parameters, nitrogenous waste levels, bacterial counts in water and organs, and total hemocyte count (THC) were analyzed. The PB treatment (multi-strain Bacillus) significantly enhanced specific growth rate (2.99±0.0027% day⁻¹), feed efficiency (57.5±0.09%), weight gain, and THC (3.80 × 10⁵ cells mm⁻³) compared to control (P<0.05). The PB and PMB treatments also reduced total ammonia nitrogen, nitrite, nitrate, and Vibrio populations in water and shrimp tissues. Intestinal colonization by beneficial bacteria was highest in PB and PL groups. These results demonstrate that specific probiotic formulations, particularly PB, can improve growth, immunity, and water quality while reducing reliance on antibiotics and water exchange. The findings support the integration of targeted probiotics in sustainable shrimp aquaculture, including biofloc and recirculating aquaculture systems (RAS).